Relationships between anthropometric and physiological characteristics with throwing velocity and on water jump of female water polo players - Platanou, T.; Varamenti, E. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The aim of this study was to examine the relationship between the anthropometric, the physiological, as well as performance related characteristics of elite female water polo players and the two important technical game parameters such as throwing velocity and on water jump. METHODS:Thirty-three female professional water polo players (age:21.7±5.4 years, height: 171.5±5.8 cm, body mass: 65.5±8.0 Kg) members of the top four teams of the Greek A1 women league were assessed for anthropometric and body composition characteristics, for physiological and performance related characteristics as well as technical characteristics. All tests were completed a month prior to an extremely important sport event. RESULTS:The percentage of body fat was 23.6±7.0 % and lean body mass was 50.0±5.6 kg. VO2peak was 47.5±5.8 ml/kg ·min, La peak 7.50±1.50 mmol/l and the swimming speed at 25-m sprint test as an indicator of the anaerobic power was 1.76±0.1 m/s. The throwing velocity was 15.54±0.71 m/s and vertical jump on water 61.65±3.68 cm. External-internal rotator muscles torque showed about a 1:1 ratio. Body lengths, swimming speed, internal-external torque of shoulder muscles as well as VO2 were significantly correlated with ball throwing velocity (r=0.36 to r=0.70, P<0.05). Body composition and swimming speed were associated with the on-water jump (r=0.34 to r=0.72, P<0.05). CONCLUSION. Knowledge of the physiological and anthropometric features that correlate with the two mainly used techniques in water-polo (throwing velocity and on water jump) can be used by coaches to implement effective training programs.